Winegrowers' decision-making: A pan-European perspective on pesticide use and inter-row management. (August 2022) - Chen, Yang; Herrera, Rafael Alcalá; Benitez, Emilio; Hoffmann, Christoph; Möth, Stefan; Paredes, Daniel; Plaas, Elke; Popescu, Daniela; Rascher, Silke; Rusch, Adrien; Sandor, Mignon; Tolle, Pauline; et al.
Abstract: European viticultural landscapes not only support a significant share of rural livelihoods and cultural traditions, but also conserve biodiversity and sustain various ecosystem services. Winegrowers' practices of inter-row management (including whether to have vegetation in the inter-rows, type of vegetation, duration of vegetation cover, and soil tillage) and pesticide use (including herbicides in the inter-rows, fungicides, insecticides, and pheromone dispensers as an alternative) can affect these services. This study aims to understand winegrowers' decision-making driven by their personal characteristics, attitudes and beliefs towards viticultural practices, physical properties of vineyards, and farm management characteristics in five European winegrowing regions. These include Palatinate in Germany, Leithaberg in Austria, Tarnave in Romania, Bordeaux in France, and Montilla-Moriles in Spain. Based on a questionnaire survey, we constructed decision trees for each behaviour per case study as well as in a generic European model. We found factors that best explain how winegrowers manage their inter-rows and use pesticides. Results showed that not only do behaviours of winegrowers vary drastically across the case studies, but also the factors that explain most behaviours: farmers' attitudes and beliefs and farm management characteristics. This implies the importance of attitudes and beliefs – which are under-researched as compared to other factors – in understanding farmers' behaviour. With the driving factors found to vary per case study, our results also imply the need for locally-adapted policies. Furthermore, our results suggest that the effects of climate change on European viticultural landscapes concern not only shifting production regions and changes in yields, but also changing pressure of pests and diseases. Any long-term behavioural change requires efforts from many stakeholders. Graphical abstract: Image 1 Highlights: Knowledge on winegrowers' decision making is needed for more sustainable practices. We explored differences in, and drivers of, inter-row management and pesticide use. Inter-row management and pesticide use differ in five European viticultural cases. Farmers' attitudes and beliefs and management properties drive behaviour. Locally-adapted policies are needed for greener inter-rows and less pesticide use.